Providing mammography in workplaces improved screening rates: cluster randomized controlled trial. (20th October 2021) - Shima, A; Tanaka, H; Okamura, T; Nishikawa, T; Godai, K; Kimura, T; Tatsumi, Y; Morino, A; Kawatsu, Y; Miyamatsu, N
Abstract: Background: Despite sufficient evidence on the importance of breast cancer screening, the screening rate has remained less than 50% in Japan. To promote behavioral change of individuals, it is important to reduce barriers to taking screening. The purpose of this study was to examine the effect of an environmental approach providing opportunities for mammography (MMG) in workplaces. Methods: Female employees aged 40 years or older were eligible. Supermarket stores were randomly assigned into two groups, the intervention arm (leaflet and MMG) and the control arm (leaflet). From May to July 2018, participants in the intervention arm were given a leaflet informing the subsidies for breast cancer screening and were provided the opportunity to have MMG in their workplace. Participants in the control group were given the same leaflet, but they had to take the screening outside the workplace as usual. The primary outcome was the breast cancer screening rate in 2018, evaluated using self-administered questionnaires. The odds ratio (OR) and 95% confidence intervals (CIs) for the screening rate in the intervention arm compared with the control arm was estimated using multilevel logistic regression. Results: We analyzed 1624 participants (mean age was 53 years) from 25 supermarket stores (intervention: 578 patients in 8 stores, control: 1046 patients in 17 stores). The screening rate in the intervention arm was 312 (54%) and was 125 (12%) in the control arm. The OR (and 95% CIs) was 7.81 (5.03-12.12) in the final model adjusted store level effects (i.e., stores and screening rate in 2017 at each store) and individual age and current smoking. Conclusions: In a worksite-based cluster-randomized controlled trial conducted in a Japanese population, an environmental approach providing MMG opportunities in workplaces significantly increased the self-reported breast cancer screening rate within one year. (UMIN000030465) Key messages: Providing the opportunity of mammography in Japanese supermarket stores improved the breast cancer screening rate. An environmental approach reducing barriers to screening may be more effective than conventional approaches in improving breast cancer screening rate.